Formalin-Fixed Fish Larvae Could Be Effectively Identified by DNA Barcodes: A Case Study on Thousands of Specimens in South China Sea - Hou, Gang; Chen, Yanying; Wang, Sijin; Wang, Jinrun; Chen, Weitao; Zhang, Hui (Frontiers in Marine Science, 2021)
Delimiting ichthyoplankton is fundamental work for monitoring the recruitment process and identifying the spawning and nursing grounds of fishes. Nevertheless, it is extremely difficult to identify the fish during the early stages at the species level based on morphological characters due to the paucity of diagnostic features. In this study, we investigated the fish larval community through large-scale ecosystemic sampling in the South China Sea (SCS) during 2013 and 2017 using DNA barcodes. To maintain the morphologies of fish larvae, we preserved the larvae in formalin and developed a technique to recover their DNA. Among the 3,500 chosen larvae, we successfully extracted DNA from 2,787 larval samples and obtained 1,006 high-quality sequences. Blast searches showed that 408 larvae (i.e., 40.5%) could be unambiguously identified to species, 413 larvae (i.e., 41.1%) were ambiguously species delimitation and 185 larvae (i.e., 18.4%) showed a low match similarity with target sequences. A total of 101 species were identified, among which 38 and 33 species corresponded to demersal and reef-associated species, while the remaining 30 species corresponded to benthopelagic, pelagic-oceanic, bathypelagic and pelagic-neritic species. High-quality larval photographs of the 101 diagnosed species showed intact morphological characters and thus provided a reference for identifying fish species during the early stages based on morphological characters. Our study highlighted the possibility of recovering and amplifying DNA from formalin-fixed samples and provided new insight into the fish larval community in the SCS.